LIBRARY AND INFORMATION SCIENCE EDUCATION IN BRUNEI DARUSSALAM: THE NEEDS AND PROSPECTS - Haji Muhammad Shariff, Tahira (Malaysian Journal of Library and Information Science, 2003)
Discusses the present situation of libraries and the needs for library and information science (LIS) education in Brunei Darussalam. LIS education at the tertiary level has not been established in Brunei. Many libraries do not have qualified library staff. Universiti Brunei Darussalam (UBD) Library, being the biggest library in the country, undertakes major initiatives in assisting development of other libraries by providing training and consultancy, and conducting LIS courses. The development of LIS education in Brunei Darussalam looks promising although establishing it at tertiary level will be a great challenge to educators and librarians alike.